PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP MINAT PEMBELIAN ULANG DI RESTORAN ANESKA ACEH TAMIANG - Antika, Putri; Nursanjaya; Sufi (Jurnal PubBis, 2024)
Repurchase behavior in restaurants is crucial as it ensures business continuity and consistently increases revenue. To encourage customers to return, restaurants must maintain high food quality, provide friendly service, and create a comfortable atmosphere. Factors that may deter customers from repurchasing include negative dining experiences, unsatisfactory service, prices that do not align with quality, and a lack of cleanliness and comfort. This research aims to analyze the impact of service quality on repurchase intention at Aneska restaurant, as well as the effect of product quality on repurchase intention at the same establishment. Additionally, the study seeks to determine the combined influence of service quality and product quality on repurchase intention at Aneska restaurant. This study employs a quantitative research approach. The population consists of all customers of Aneska restaurant, with a sample of 97 respondents selected using the Lemeshow formula. Data collection was conducted using a Likert scale. The first stage of instrument testing involved validity and reliability assessments. Subsequent data analysis techniques included classical assumption tests, multiple linear regression analysis, and hypothesis testing. The findings indicate that service quality has a positive and significant impact on repurchase intention. Product quality also has a positive and significant effect on repurchase intention. Moreover, service quality and product quality together have a positive and significant impact on repurchase intention at Aneska restaurant. Based on these results, Aneska restaurant is recommended to focus on employee training to enhance service and to ensure that food and beverages are consistently prepared to high-quality standards. Keywords: Service Quality, Product Quality, Repurchase Intention